Conscientiousness and Civic Virtue in Organizational Citizenship Behavior Toward Organizational Commitment at the Regional Secretariat of the West Papua Provincial Government - Karim, Yusuf Abdul; Ibrahim, Muhammad Akmal; Ahmad, Badu (KnE Social Sciences, 2025)
Organizational citizenship behavior, is one of the driving factors for State Civil Apparatus in showing better organizational commitment. This study aims to explain conscientiousness and civic virtue in organizational citizenship behavior toward organizational commitment at the Regional Secretariat of the West Papua Provincial Government. This study uses a descriptive qualitative approach. Data collection methods include observation, in-depth interviews, and documentation. Research informants consist of State Civil Apparatus working in the Regional Secretariat of the West Papua Provincial Government and several Bureau Chiefs in the agency. This study shows that there are still State Civil Apparatus who tend to find it difficult to work and experience stress at work, but they still try to show commitment to achieving organizational goals. State Civil Apparatus who demonstrate civic virtue in the Regional Secretariat show a desire to contribute more than just carrying out their daily duties because they feel they have a responsibility toward the organization’s future. This shows a sense of loyalty and dedication to the vision and mission of the organization.